Food neophobia and the evaluation of novel foods in adults; the sensory, emotional, association (SEA) model of the decision to taste a novel food. (1st January 2022) - Coulthard, Helen; Aldridge, Victoria; Fox, Gemma
Abstract: Reluctance to eat new foods, known as food neophobia, is well researched in children but not adults. Two studies were carried out to understand the emotional, sensory, and cognitive factors associated with food neophobia in an adult sample, and to propose a preliminary explanation of the decision to taste a novel food named the SEA model (Sensory, Emotional, cognitive Association model). Participants were recruited through opportunity sampling of a university population in the Leicester region of the UK. Study one (n = 534) was a cross sectional study examining associations between self-report measures of food neophobia, emotional variables and sensory variables. In study two (n = 160), participants completed an online cognitive evaluation of 7 images of novel fruits and vegetables, rating perceived familiarity, categorisation as fruit or vegetable, cognitive associations based on appearance (what does the food look like), liking of any associated foods, and expected liking of the novel food. In study 1 it was found that tactile sensitivity and disgust sensitivity were the main sensory and emotional variables associated with food neophobia. In study 2, it was found that food neophobia and lower expected liking of novel foods were associated with disgust sensitivity, associating the novel foods with disliked foods, and lower perceived familiarity. The SEA model further proposes that underlying tendencies and automatic reactions to foods, combine with cognitive associations based on negative memories and negative beliefs about tasting new foods, to create expected disliking of a food and a decreased likelihood that it will be tried. Further work is needed to fully test the SEA model of the decision to taste a novel food, in particular to further examine how associations are formed.